REAL 3D MODEL FOR PHYSICAL SCIENCES CONTRIBUTION TO THE CREATIVE CAPACITY OF CRITICAL THOUGHT, PERSONAL PERSCEPTION AND THE EDUCATIONAL ABILITY OF THE STUDENTS - Drougas , Vasileios Ag.; Bin-Tahir, Saidna Zulfiqar (Uniqbu Journal of Exact Sciences, 2022)
The education of students in the Natural Sciences is a special one between the theory of experimentation and reconstruction and self-control for knowledge as it has passed through the process of learning and identifying the student’s information through the learning process. There is an important relationship between the theory of experimentation and reconstruction and self-control for knowledge through the learning process. This paper presents and analyzes the research results of the thoughts of 180 students from a Department of Informatics and Telecommunications who participated in Physics experiments, workshops. The students practiced and trained through real 3D models that created especially for the theoretical lessons of physics in Telecommunications and Electromagnetism. The study of the results shows that the use of real three-dimensional education models in education can help to understand natural phenomena and laws in the fullest understanding of the theory of lessons which probably present a gap between the experimental process and the theoretical presentation. The real three-dimensional models in learning as learning models are deemed necessary and there is always a relative limitation in their use either from the time allocated to the program. Students would like to appear such models in the educational programs in their schools especially in the modern environment where the modern technologies may sometimes do not achieve critical thought, personal perception and or educational ability especially in the physical sciences that is a part of our daily life.